Improving the deadlift: Understanding biomechanical constraints and physiological adaptations to resistance exercise - Hales, M. (Strength and Conditioning Journal, 2010)
In the sport of powerlifting, incorrect information regarding muscular strength development may be perpetuated by various sources. One way to combat this problem is to provide correct biomechanical and physiological information regarding lifts such as the deadlift to enhance performance in the sport. There are 3 specific areas that can be addressed to improve deadlift performance: Supportive gear, lifting mechanics and training principles. This article offers suggestions to enhance performance in the deadlift by providing insight into physiological adaptations and biomechanical constraints associated with strength development.